Assessment of Ability of User Education in Medical Records Module of Selected HIS in Isfahan University of Medical Sciences. - Bakhsh, Saeed Saeed; Sadoughi, Farahnaz; Ehteshami, Asghar; Esfahani, Mahtab Kasai (Iranian Journal of Medical Education)
Introduction: Hospital managers and service providers need to Hospital Information System (HIS) to increase the efficiency and effectiveness of the organization its goals. The basis for decision making, policymaking and planning at different levels of hospital management (including executive management, and clinical services) is detailed, accurate, timely and reliable information, and its interpretation, and this was done through proper training software users. This study aimed to assess the ability of user education in medical records module of selected HIS in Isfahan University of Medical Sciences. Methods: This research is an applied, descriptive cross sectional study, in which ability of users training modules of medical records in seven selected HIS in Isfahan University of Medical Science hospitals was assessed. It was based on the users' experiences using ISO 9241/10 questionnaire including eight items (ranked fifth option in the Likert scale) in the second half of 1387. The International Organization for Standardization standardizes this questionnaire. Therefore, it was not possible to change questions. However, to ensure its admissibility and fitness for research environment, its content validity was confirmed (based on health information managers, health services managers, and computer science experts' view) and the reliability was confirmed by test-retest (r =95%). The data gathering was done through referring directly to centers and training face to face all users (40 users), and then completing questionnaires. Data collected analysis was done by descriptive analysis (central tendency indices) and their standardization (converting to the relative frequency). Finally finding were classified in three categories including optimal (100% -81%), good (80% - 51%) and unfavorable (50% -0%). Results: Data analysis showed that the time needed to learn how to use the system was unfavorable (48%), easy relearning of how to use this system after long term was desired (8/85%), support of system for user training was relatively desirable (68%), the lack of problems in learning rules for user relation with software was fairly good (8/78%). In addition, correct use of the software without asking colleagues was (60%) relatively favorable, encouraging users to test system performance with trial and error was (4/73%) relatively good, requiring to remember too much detail to use software correctly was (4/56%) fairly good, easy use of commands was (80%) fairly good, user education was (8/68%) fairly. Conclusion: According to the findings, it seems that software developers should decrease time needed for learning how to use the system, allow users to learn with HIS, answer users potential questions, allow testing system performance with trial and error, allows easy application of commands, and decrease problems about learning user communication with system in order to increase training ability.